Extracellular Vesicles in Skin Wound Healing - Deimantė Narauskaitė; Gabrielė Vydmantaitė; Justina Rusteikaitė; Revathi Sampath; Akvilė Rudaitytė; Gabija Stašytė; María Isabel Aparicio Calvente; Aistė Jekabsone (MDPI AG, 2021)
Each year, millions of individuals suffer from a non-healing wound, abnormal scarring, or injuries accompanied by an infection. For these cases, scientists are searching for new therapeutic interventions, from which one of the most promising is the use of extracellular vesicles (EVs). Naturally, EV-based signaling takes part in all four wound healing phases: hemostasis, inflammation, proliferation, and remodeling. Such an extensive involvement of EVs suggests exploiting their action to modulate the impaired healing phase. Furthermore, next to their natural wound healing capacity, EVs can be engineered for better defined pharmaceutical purposes, such as carrying specific cargo or targeting specific destinations by labelling them with certain surface proteins. This review aims to promote scientific awareness in basic and translational research of EVs by summarizing the current knowledge about their natural role in each stage of skin repair and the most recent findings in application areas, such as wound healing, skin regeneration, and treatment of dermal diseases, including the stem cell-derived, plant-derived, and engineered EVs.